A new methodology for deformable object simulation - Zhong, Yongmin; Shirinzadeh, B.; Alici, G.; Smith, J. (IEEE, 2005)
This paper presents a new methodology for the deformation of soft objects by drawing an analogy between heat conduction and elastic deformation. The potential energy stored in an elastic body as a result of a deformation caused by an external force is propagated among mass points by the principle of heat conduction. An improved heat conduction model is developed for propagating the energy generated by the external force in a natural manner. A method is presented to derive the internal forces from the potential energy distribution. This methodology not only deals with large-range deformation, but also accommodates both isotropic and anisotropic materials by simply changing thermal conductivity constants. Examples are presented to demonstrate the efficiency of the proposed methodology.